Changing children’s lives: risks and opportunities - Pells, Kirrily (2014)
Children’s development and well-being are significantly influenced by their family and community environment, with poor and marginalised children facing a heavier burden of risk. This paper summarises emerging findings from the Young Lives longitudinal study of childhood poverty in Ethiopia, the state of Andhra Pradesh in India, Peru and Vietnam. It examines how children’s development is shaped by different environmental influences, highlighting the changes in children’s daily lives during the first decade of the twenty-first century, including the changing nature of risks and opportunities.